Phantasia and Technè at the Fin-de-siècle - Uricchio, William (Intermédialités / Intermediality, 2005)
The essay provides a reconsideration — both at a theoretical and at an historical level — of the televisual as a mean to extend the viewer's engagement and interaction with the world, as opposed to other media's (i.e. cinema, photography, recorded music) incapacity to afford an experience of liveness and temporal simultaneity. It engages not only in the question of the development of media and the ontological differences among media, but also the wider epistemological issue of the relevance of technology to our understanding of modernity. The essay is grounded in Husserl's and Heidegger's discussions of the relationship between technè and modernity, draws upon the historical case of Nazi television, and among other things, explores the subject-object and presence-representation dichotomies.